Pendapatan Perempuan Terhadap Kemiskinan dan Ketimpangan: Bukti Data Panel dari Provinsi Bali - Susilo, Edi; Ginting, Yanti Mayasari; La Basri (Jurnal EMT KITA, 2024)
This research aims to analyze the influence of women's income on poverty levels and income inequality in the province of Bali. Using panel data from 9 city districts during the 2011-2022 period, the analytical model applied to test the functional relationship between variables is panel regression with a fixed effect approach. The research results reveal that women's income cannot significantly reduce poverty levels, but can improve income distribution in society. These findings have implications that efforts to reduce levels of inequality and poverty in the province can create an economic empowerment program that is oriented towards increasing women's income.